Metabolic engineering of p‐hydroxybenzoate in poplar lignin. Issue 1 (25th October 2022) - Mottiar, Yaseen; Karlen, Steven D.; Goacher, Robyn E.; Ralph, John; Mansfield, Shawn D.
Summary: Ester‐linked p ‐hydroxybenzoate occurs naturally in poplar lignin as pendent groups that can be released by mild alkaline hydrolysis. These 'clip‐off' phenolics can be separated from biomass and upgraded into diverse high‐value bioproducts. We introduced a bacterial chorismate pyruvate lyase gene into transgenic poplar trees with the aim of producing more p ‐hydroxybenzoate from chorismate, itself a metabolic precursor to lignin. By driving heterologous expression specifically in the plastids of cells undergoing secondary wall formation, this strategy achieved a 50% increase in cell‐wall‐bound p ‐hydroxybenzoate in mature wood and nearly 10 times more in developing xylem relative to control trees. Comparable amounts also remained as soluble p ‐hydroxybenzoate‐containing xylem metabolites, pointing to even greater engineering potential. Mass spectrometry imaging showed that the elevated p ‐hydroxybenzoylation was largely restricted to the cell walls of fibres. Finally, transgenic lines outperformed control trees in assays of saccharification potential. This study highlights the biotech potential of cell‐wall‐bound phenolate esters and demonstrates the importance of substrate supply in lignin engineering.